The Effect of Urea and Sulphur Level in Mixing of Cassava Waste Fermented and Soybean Cake waste on Nitrogen Balance and Digestibility of Energy of Local Male Sheep - Haryanto, Budi; Hidayat, Nur; Bata, M (ANIMAL PRODUCTION, 2001)
Cassava waste and soybean cake waste are by - product from home industry  that  have been used as animal feed. It contain high crude fibber, there fore it must be processed or added with another nutrients before feeding to animal to get a good performance. A research have been  conducted in Experimental Farm and Laboratory Animal of  Feed and Nutrition, Animal Science Faculty, Jenderal Soedirman University, Purwokerto at October- Nopember 2001. The purpose of  the research is to find the effect of urea and sulfur  level in mixing of cassava waste fermented and soybean cake waste on nitrogen balance and digestibility of energy of local male sheep. Eighteen local male sheep were  divided into 3 group based of the body weight. There are I = 18.55±1.27 kg, II = 15.79±0.67 kg and  III = 13.41±1.33 kg. Two level of urea (2% and 3%) and three level of sulfur (0 %, 0.15 % and 0.30%) dry matter concentrate used as  treatments, there fore factorial   design 2x3 with Randomized Block Design used this experiment All of treatment received same diet consist land grass and concentrates with 70:30 dry matter ratio. Concentrates consists  cassava waste fermented  and soybean cake waste with 77.50:22.50 dry matter ratio.  Dry matter intake was 4 % body weight. Observed variables were nitrogen balance and digestibility of energy by using total collection. Variance analysis was used for knowing the effect treatment on the variable observed. The result of the research shown that level of urea and sulfur are not significant interaction on the nitrogen balance and digestibility of energy.  However  level urea and sulfur  itself are significant on nitrogen balance linearly. Level urea also had significant effect on the energy digestion.  Balance nitrogen of all treatment is positive. Level of urea 3 % and sulfur 0.30% gave a good balance nitrogen and energy digestion.  It can be concluded that addition of urea and sulfur in diet containing fermentable  carbohydrates can increase balance nitrogen (N retention) and energy digestion. (Animal Production 3(2): 91-97 (2001)Key Words: Balance nitrogen, energy digestion, cassava waste and soybean cake waste